Types Of Interviews In Non-Test Behavioral Assessment Instruments - Salsabila, Bilqis; Suhartini, Brigita; Khoirani; Qanitha, Amira Dwi; Fitria, Sarvika Ananda; Putri, Mayang Kusuma (Journal of Therapia, 2024)
This study discusses the important role of interviews in non-test Guidance and Counseling (BK) instruments, particularly in measuring the behavioral domain of individuals. Interviews are an effective method for understanding individuals' thoughts, feelings, and experiences, as well as the psychological, social, and environmental aspects that influence behavior. This study aims to provide an in-depth understanding of the types of interviews in non-test counseling instruments and their impact on the effectiveness and validity of information obtained in the guidance and counseling process. The research method uses a multiple case study approach to analyze several individual or group cases in the context of behavioral domain assessment. Data were collected through in-depth interviews, direct observation, and related documentation. The analysis identified the types of interviews used in non-test counselling instruments and their categorization based on their characteristics and benefits. The conclusion states the importance of understanding the types of interviews in the context of non-test BK to improve guidance and counseling practices.